2012
DOI: 10.5539/ibr.v5n5p116
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of Competitive Capability’s Contribution toward Firm Performance: Moderating Role of Perceived Environmental Uncertainty

Abstract: In the world of competition, manufacturing and service companies are trying to enhance their competitive capabilities in order to be able to give more value to their customers and gain prominent positions in competition with other companies. Every company tries to concentrate on its one or more capabilities in competition in order to turn them into a clear competitive advantage that improves the firm performance. In fact, it is necessary for the firms being active in market and being consistent with competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…The study of PEU on firm's performance has been documented for decades (Alvarez and Barney, 2005;Bacha, 2010;Cannella et al, 2008;Hosseini and Sheikhi, 2012;Matanda and Freeman, 2009;Ondersteijn et al, 2006;Ruzita, 2010), and the effect of PEU on firm performance has rapidly increased in the past 10 years. This is not surprising as the business marketplace is extremely competitive and the macro environmental factors, such as economic and political situations, often fluctuate.…”
Section: Environmental Uncertainty and Performancementioning
confidence: 99%
“…The study of PEU on firm's performance has been documented for decades (Alvarez and Barney, 2005;Bacha, 2010;Cannella et al, 2008;Hosseini and Sheikhi, 2012;Matanda and Freeman, 2009;Ondersteijn et al, 2006;Ruzita, 2010), and the effect of PEU on firm performance has rapidly increased in the past 10 years. This is not surprising as the business marketplace is extremely competitive and the macro environmental factors, such as economic and political situations, often fluctuate.…”
Section: Environmental Uncertainty and Performancementioning
confidence: 99%
“…Another thing that urge for Indonesia's plywood industry to do is to restructure the preparation of policies and better infrastructure. Business competition in the era of globalization is characterized by market instability, perceived environmental uncertainty (PEU), require companies to conduct both of competitive advantage in terms of price and quality [3].…”
Section: Roja Fitridayani 2 Widyatama University Bandung Indonesiamentioning
confidence: 99%
“…Earlier studies have demonstrated that the accelerated changes in technology, markets, regulations, and hyper-competition have made the business environment become uncertain and unpredictable (Hosseini & Sheikhi, 2012), causing turbulence environment that can lead to competitive advantage becomes eroded (Irbansyah, 2011) and difficult to maintain (D'Aveni, Dagnino, & Smith, 2010).…”
Section: Introductionmentioning
confidence: 99%